A Study on the Influence of FDM Parameters on the Tensile Behavior of Samples made of ASA - Zisopol, Dragos Gabriel; Minescu, Mihail; Iacob, Dragos Valentin (Engineering, Technology & Applied Science Research, 2024)
This paper presents the results of the study on the influence of FDM printing parameters on the tensile behavior of samples made of ASA. To perform the study, 27 tensile samples were made of ASA on Anycubic 4 Max 2.0 3D printer using as the height of the single-pass layer Lh = 0.10/0.15/0.20 mm and as filling percentage Id = 50/75/100%. The results obtained from tensile testing of the samples on the universal testing machine demonstrate the way in which the FDM parameters influence the tensile strength, the percentage elongation at break, and the elastic modulus. The parameter that significantly influences the tensile characteristics of ASA samples made using FDM is the filling percentage (Id).